If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + 8 = -5(6x + -5) Combine like terms: 17 + 8 = 25 25 = -5(6x + -5) Reorder the terms: 25 = -5(-5 + 6x) 25 = (-5 * -5 + 6x * -5) 25 = (25 + -30x) Add '-25' to each side of the equation. 25 + -25 = 25 + -25 + -30x Combine like terms: 25 + -25 = 0 0 = 25 + -25 + -30x Combine like terms: 25 + -25 = 0 0 = 0 + -30x 0 = -30x Solving 0 = -30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30x' to each side of the equation. 0 + 30x = -30x + 30x Remove the zero: 30x = -30x + 30x Combine like terms: -30x + 30x = 0 30x = 0 Divide each side by '30'. x = 0 Simplifying x = 0
| 4(3x+6)=-28+4 | | 5x^3-45x^2+70x=0 | | -4/x-1=5/(2x-1) | | 3(3x+2)=-5(4x-2)+2x | | 15/(5/9)= | | 2x+15=9x+36 | | 3x-2=8+2x | | 12-(10x)+3x-(-10)= | | 36b^2-121g^2= | | 4r^2+12rt+9t^2= | | 8x^2-10x-25= | | 4f/58 | | 23-6=x | | 7x^2+79x+22=0 | | f(pi/6)=2sin(pi/6)-cos2(pi/6) | | 8=4xq | | 15b^2-21b-72= | | 12x^2-11x-36= | | 2*sin(pi/6) | | 4x-15+2x-10=37 | | 100a^2-196= | | (x-1)(x+5)=5 | | 2x-x^2+24=0 | | 2x^3-6x^2-56x= | | 2x^2+6x-4= | | 2x^3+5x-13=0 | | x^3+3x^2-40x= | | (2x+3)=(75-2x) | | 5y-26=-6+9y | | 3(x*x)=243 | | ln(y^2+15)=ln(y+3)+ln(y) | | -x^2-11x-30= |